Highly efficient antireflective and self-cleaning coatings that incorporate carbon nanotubes (CNTs) into solar cells: A review - Hanaei, H. (Elsevier Ltd, 2016)
Due to their useful atomic structure, carbon nanotubes (CNTs) have fascinating chemical and physical properties, as exemplified by graphite and diamond. They have enabled major achievements in various fields, such as materials, electronic devices, energy storage, separations, and sensors. Recently, antireflective coatings (ARCs) with self-cleaning properties have been studied because of their interesting characteristics and wide variety of practical applications. In this review, the basic principles of antireflection and self-cleaning are discussed. Fabrication methods are also discussed, with specific attention given to silicon and silica substrates that incorporate CNTs. Additionally, ARCs and self-cleaning coatings on carbon nanotubes are briefly described. Finally, recent developments in antireflective and self-cleaning coating using CNTs and some multifunctional ARCs are introduced. Â© 2016 Elsevier Ltd. All rights reserved.